Third order differential subordination associated with exponential function - Judy Lavanya, V. Agnes Sagaya; Jeyaraman, M. P.; Rajakumar, M. P. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5Using admissibilty conditions, we investigate some third-order differential subordination results with a superordinate function $q(z)=e^z$. As an application,  we obtain sufficient conditions for certain special functions to become exponential convex and exponential starlike. The derived second-order differential implications significantly generalize numerous results obtained in [A. Naz, S. Nagpal, V. Ravichandran, Mediterran.  J. Math., 17, № 204, 1–22 (2020)].